Bone Mineral Density Measurement in Menopausal Women Presenting with Low Back Pain: A Prospective Study (TAJ: Journal of Teachers Association, 2009)
Bone mineral densitometry was done in 107 women in their post-menopausal period using Dualenergy X-ray absorptiometry method. All the patients were presented with low back pain.Quantification of bone mineral density was done in proximal femur and lumber spines of all thepatients. Sixty-eight patients showed normal bone mineral density in our study. Rest 39 patientsshowed declination of bone mineral density from mild osteopenia to severe osteoporosis. Weconclude that Dual energy X-ray absorptiometry bone mineral measurement is an unique, noninvasivemethod of detecting bone mass disorder in post-menopausal women with low backpain and should be the first choice of investigation.doi: 10.3329/taj.v15i2.3909TAJ December 2002; Vol.15(2):64-67